Multilingual Practices in Higher Education: The Effectiveness of Ubuntu Translanguaging for Language Acquisition - Soyiso Godsave Khetoa (JOLLT Journal of Languages and Language Teaching, 2026)
Monolingual approaches to language learning proves inconsequential in teaching an African language to a cohort of students who have limited access to the language of teaching and learning. This study aims to examine the effectiveness of students’ repertoires in L2 classroom. The study further seeks to establish how students make use of non-target languages to support language learning. This study is underpinned by ubuntu translanguaging as a pedagogical approach which is applied in the classroom setting to enhance learning. This study employs a qualitative approach by applying a document analysis approach. The findings indicate that the use of non-target languages in the classroom is used as a resource for meaning making, provides ontological access to disciplinary content, and that this approach empowers students within the language learning context. Therefore, the use of non-target languages is an inescapable reality in a time sensitive learning environment. Moreover, it has been determined that the use of non-target language(s) are an important component in the process of meaning-making. This study promotes the use of ubuntu translanguaging as a decolonial pedagogy which enhances access, meaning making, and student empowerment in an African language classroom. The study actively advocates for pedagogical transformation and a curriculum design rethink in the teaching and learning of an African languages as an additional language.